Pengaruh Edukasi Perilaku Hidup Bersih dan Sehat melalui Program GEMBIRA pada Anak Usia Sekolah di RW 08, Desa Sukorambi, Jember - Idfiana Hilmi; Riza Rohmatul Maulidia; Tantut Susanto; Yuyus Febsyna (Caring : Jurnal Keperawatan, 2025)
Diarrhea is one of the gastrointestinal infectious diseases that is still a public health problem in Indonesia. This disease can affect all age groups, but elementary school children are the most vulnerable group due to an imperfect immune system and hygiene behavior that has not been well established. This community service activity carried out by students of the Nursing Professional Education Study Program aims to increase knowledge and behavior of clean and healthy living through the GEMBIRA program (Gerakan Membiasakan Bersih dan Rajin pada Anak) which is carried out in RW 08 Krajan Hamlet, Sukorambi Village. The targets in this study were school-age children in RW 08 Krajan Hamlet, Sukorambi Village, Jember Regency. The program provided health education, a demonstration of hand washing and tooth brushing, a group therapy quiz, and child empowerment through drawing activities. The analysis results showed an increase in children's knowledge and behavior in four main indicators after the intervention was given. Knowledge about diarrhea increased from 22.7% to 82%, proper tooth brushing from 18.2% to 50%, healthy snack consumption from 18.2% to 68.2%, and hand washing behavior from 27.3% to 81.8%. Wilcoxon test showed that all differences before and after the intervention were significant (p < 0.05). These results indicate that the GEMBIRA program is effective in improving the understanding and behavior of PHBS in children. The continuation of the health education program is expected to be a preventive measure to improve the quality of health of school-age children.